The Flat Landing Brook Zn-Pb-Ag Massive Sulfide Deposit, Bathurst Mining Camp, New Brunswick, Canada - J. A. Walker; D. R. Lentz (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"Abstract -The Flat Landing Brook Zn-Pb-Ag deposit of the Bathurst Mining Camp occurs within a narrow thrust-bound nappe containing felsic volcanic and volcaniclastic rocks of the Tetagouche Group. Within the host nappe, the Tetagouche Group is represented by the Nepisiguit Falls Formation and the overlying Flat Landing Brook Formation. The Nepisiguit Falls Formation is divided into two members: quartz- and quartz-feldspar-phyric volcaniclastic rocks ± minor lavas (Grand Falls member), and aphyric, fine-grained volcaniclastic rocks (Little Falls member). The Flat Landing Brook Formation consists of aphyric rhyolite flows and interbedded pyroclastic rocks. Several gabbroic intrusions occur in both the footwall and hanging-wall sequences. These gabbros locally cut out the mineralized horizon at shallow levels, and are considered to be feeders to tholeiitic basaltic flows (Forty Mile Brook member) of the Flat Landing Brook Formation. The Flat Landing Brook deposit has many of the characteristics typical of volcanogenic massive sulfide deposits occurring within the highly productive Nepisiguit Falls Formation in the eastern part of the Bathurst Mining Camp. Mineralization occurs within or at the top of the Grand Falls member and comprises four or more massive to semi-massive sulfide lenses that vary in thickness between 3 and 5 m. Massive lenses are laterally gradational to, or underlain by, zones of disseminated sulfides up to 38 m thick. The deposit contains an estimated resource of 1.7 Mt grading 4.9% Zn, 0.94% Pb, and 19.54 g/t Ag to a depth of approximately 150 m. From 150 to 300 m below surface, mineralization is low grade and mostly disseminated. However, below 300 m, ore-grade (>10% Pb+Zn) massive sulfide lenses have been intersected over mineable widths. Oxide facies iron formation overlies and (or) grades laterally into the sulfide lenses. The oxide facies has strong positive Eu anomalies and gently sloping rare earth element (REE) profiles suggesting that it was formed from relatively hot acidic fluids that had interacted with felsic volcanic rocks in the footwall. In contrast, the silicate facies iron formation that is more distal to sulfide accumulations has very weak positive Eu anomalies and gently sloping REE profiles, suggesting either cooler hydrothermal fluids or dilution of the hydrothermal component by detrital material. Hydrothermal alteration has affected most footwall rocks. Most notably, albite-destructive alteration has resulted in Na2O depletion, whereas mass addition of K2O is manifested in the formation of sericite (white mica). In more intensely altered quartz- and feldspar-phyric volcaniclastic rocks of the Grand Falls member, feldspar destruction is accompanied by chlorite alteration, producing quartz-phyric rocks similar to those in the footwall of many Bathurst Camp deposits."